2016
DOI: 10.7150/jca.13749
|View full text |Cite
|
Sign up to set email alerts
|

Chromobox Homolog 4 is Positively Correlated to Tumor Growth, Survival and Activation of HIF-1α Signaling in Human Osteosarcoma under Normoxic Condition

Abstract: Objectives: The clinical significance and tumorigenesis of Chromobox homolog 4 (CBX4) have been reported in hepatocellular carcinoma. The purpose of this study is to confirm the expression, elucidate the biological function and investigate the potential mechanism of CBX4 in osteosarcoma (OS). Methods: The expression of CBX4 in OS samples and cell lines was measured by RT-PCR and western blot test. Cell cycle, CCK8 and colony-forming assays were used to detect changes of cells growth. Cell apoptosis assay was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…CBX4 expression varies in different types of cancer and has diverse biological functions. It is a cell cycle promoting gene with proliferative activity and is found in the epithelium; this protein is found to be up‐regulated and exhibits pro‐tumour effect by activating the HIF‐1α signalling pathway in osteosarcoma . In our study, we demonstrated that the expression of CBX4 in lung tumour tissues was significantly higher compared with adjacent cancer tissues (Figure A,B).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…CBX4 expression varies in different types of cancer and has diverse biological functions. It is a cell cycle promoting gene with proliferative activity and is found in the epithelium; this protein is found to be up‐regulated and exhibits pro‐tumour effect by activating the HIF‐1α signalling pathway in osteosarcoma . In our study, we demonstrated that the expression of CBX4 in lung tumour tissues was significantly higher compared with adjacent cancer tissues (Figure A,B).…”
Section: Discussionsupporting
confidence: 49%
“…It is a cell cycle promoting gene with proliferative activity and is found in the epithelium; this protein is found to be up-regulated and exhibits pro-tumour effect by activating the HIF-1α signalling pathway in osteosarcoma. 16,22,23 In our study, we demonstrated that the expression of CBX4 in lung tumour tissues was significantly higher compared with adjacent cancer tissues ( Figure 1A,B). Meanwhile, higher CBX4 expression was positively correlated with tumour size, clinical stage and lymph node metastasis (Table 1).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Knockdown of CNOT1 could inhibit Hedgehog signaling pathway. Activation of the Hedgehog signaling pathway has been implicated in the development of many human malignancies, including prostate cancer (Xu et al, 2014), ovarian cancer (Li et al, 2016), and breast cancer (Zhou et al, 2016). Overexpression of LMNA could rescue CNOT1 knockdown-mediated tumor inhibition and Hedgehog signaling pathway inhibition.…”
Section: Introductionmentioning
confidence: 99%